2011
DOI: 10.1007/s12149-011-0544-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of breast-specific gamma imaging as an adjunct modality in breast cancer patients with dense breast: a comparative study with MRI

Abstract: BSGI showed an equivocal sensitivity and a high specificity compared to MRI in the diagnosis of breast lesions. In addition, BSGI had a good sensitivity in discriminating breast cancers ≤1 cm. The results of this study suggest that BSGI could play a crucial role as an adjunctive imaging modality which can be used to evaluate breast cancer patients with dense breasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…Also, Kim included 66 patients with dense breasts and already biopsyconfirmed breast cancer. This study reported a percentage of 88.8% sensitivity and 90.1% specificity of BSGI; while MRI sensitivity and specificity were 92.3% and 39.4% respectively [17]. In the other hand, Keto, et al enrolled only 18 patients, having Ductal Carcinoma-In-Situ, who underwent both breast MRI and BSGI and found that the sensitivity for BSGI was 89% and for MRI was 94% [18].…”
Section: Resultsmentioning
confidence: 84%
“…Also, Kim included 66 patients with dense breasts and already biopsyconfirmed breast cancer. This study reported a percentage of 88.8% sensitivity and 90.1% specificity of BSGI; while MRI sensitivity and specificity were 92.3% and 39.4% respectively [17]. In the other hand, Keto, et al enrolled only 18 patients, having Ductal Carcinoma-In-Situ, who underwent both breast MRI and BSGI and found that the sensitivity for BSGI was 89% and for MRI was 94% [18].…”
Section: Resultsmentioning
confidence: 84%
“…6,121,122 In a comparison of BSGI with MRI used in preoperative evaluation, the sensitivities of the two techniques were similar (89% and 92%) but BSGI demonstrated significantly better specificity of 90% compared to 39% for MRI (p < 0.0001). 123 A study performed using a dedicated CZT-based MBI system and 99m Tc-tetrofosmin in 264 patients showed gamma imaging to significantly improve detection of multifocal or multicentric disease compared to that detected with mammography (88% vs 48% of cases, p < 0.0005) and to correctly alter surgical management in 16% of patients. 124 Preliminary results from a similar study using a dual-head version of the CZT-based MBI system and reduced doses of ∼300 MBq 99m Tc-sestamibi were reported: gamma imaging detected additional disease not appreciated by mammography and ultrasound in 12 of 98 patients (12%), which altered surgical management.…”
Section: Ivb Preoperative Evaluationmentioning
confidence: 99%
“…Several studies have demonstrated that BSGI and DEC-MRI have similar sensitivity and specificity in breast cancer detection (12,13). However, little is known about the correlation of 99mTc-MIBI uptake in BSGI with DCE-MRI parameters of breast cancer.…”
Section: Mri Is An Effective Diagnostic Tool For Differentiation Betweenmentioning
confidence: 99%